CIRCULAR ECONOMY AND ITS POTENTIAL TO REDEFINE SUSTAINABLE INVESTMENT PRACTICES - Muh. Nur; Rafaela Lima; Felipe Souza (Journal Markcount Finance, 2026)
The circular economy has gained increasing prominence as a transformative framework aimed at decoupling economic growth from resource depletion and environmental degradation. In response to mounting sustainability challenges, investors and policymakers are exploring circular economy principles as a foundation for reshaping sustainable investment practices. This study aims to analyze the potential of the circular economy to redefine sustainable investment practices by examining how circular strategies affect capital allocation, risk management, and corporate value propositions. The research seeks to clarify whether circular economy adoption functions as a driver of financial performance, environmental impact, and systemic resilience within investment portfolios. The study employs a qualitative analytical research design based on secondary data, including peer-reviewed academic literature, sustainability reports, investment frameworks, and policy documents related to circular economy implementation. The findings indicate that circular economy practices encourage longer-term investment horizons, enhance resource efficiency, and support innovation-driven value creation. The study concludes that the circular economy holds substantial potential to redefine sustainable investment practices by integrating economic, environmental, and governance considerations, while requiring supportive policy frameworks and standardized impact metrics to realize its full investment potential.